2021
DOI: 10.1007/s40812-021-00186-x
|View full text |Cite
|
Sign up to set email alerts
|

Process R&D investment and social dilemmas

Abstract: We consider a coopetitive game model of firms’ behavior in process R&D with entry cost. We compare the competitive behavior of firms in R&D with the R&D coopetition scenario. In R&D coopetition, firms engage in a bargaining process to reach a binding R&D agreement. We find that R&D competition can lead to a prisoner’s dilemma or a chicken game between market rivals. The possibility of entering a binding R&D agreement resolves the above social dilemmas associated with the firms’ comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Conti and Marini [20] found that information asymmetry may exacerbate underinvestment without R&D agreements. Ramsza et al [21] concluded that the medium level of entry cost would make firms investing in R&D betray each other.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conti and Marini [20] found that information asymmetry may exacerbate underinvestment without R&D agreements. Ramsza et al [21] concluded that the medium level of entry cost would make firms investing in R&D betray each other.…”
Section: Literature Reviewmentioning
confidence: 99%